Limit State Response of Composite Columns and Beam-Columns Part I: Formulation of Design Provisions for the 2005 AISC Specification - Leon, Roberto T.; Kim, Dong Keon; Hajjar, Jerome F. (Engineering Journal, 2007)
The 2005 Specification for Structural Steel Buildings contains substantial changes to the design of composite members and composite columns in particular. These revisions are intended to reflect the extensive research in the area of composite steel-concrete structures during the past two decades, as the previous specifications were based on studies from the late 1960s-1970s. This paper describes the databases created and the process followed to develop the new provisions. This process includes the development of both new strength equations for encased and concrete-filled columns and new interaction equations for composite beam-columns as well as considerable liberalization of local buckling and material limits. The paper also discusses other important areas of composite design, such as bond stress between steel HSS sections and concrete, where specification provisions are under development. This is the first of a two-part paper; the second part contains detailed design examples.